Investigating Failure Modes and Performance Impacts of Wet Clutches in Automotive Limited Slip Differentials - Schneider, Thomas; Völkel, Katharina; Pflaum, Hermann; Stahl, Karsten (Lubricants, 2024)
In the design of rear-axle locking differentials, the desired high locking effect is often achieved using wet multi-plate clutches. This study conducts an in-depth investigation into the spontaneous damage behavior of these clutches through a series of methodical experimental tests. It focuses on three different clutch variants, each equipped with organic friction linings—namely, paper-based, carbon composite, and woven carbon—and undertakes a comparative analysis of their respective damage typologies. The experimental analysis identifies and characterizes patterns of damage, notably the buckling of steel plates and the detachment of lining. Moreover, the study thoroughly examines and compares the friction and temperature behavior under the high load conditions applied to these three friction systems. Concurrent temperature measurements enable the establishment of robust temperature-based criteria for predicting and understanding damage behavior.
CRIS-Team Scopus Importer:2025-05-19
Keywords: carbon friction material; damage behavior; limited slip differentials; transient slip; wet clutch